2013
DOI: 10.1111/bjh.12486
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐centre retrospective study of rituximab use in the treatment of relapsed or resistant warm autoimmune haemolytic anaemia

Abstract: SummaryThis retrospective analysis assessed the response, safety and duration of response to standard dose rituximab 375 mg/m 2 weekly for four weeks as therapy for patients with primary or secondary warm autoimmune haemolytic anaemia (WAIHA), who had failed initial treatment. Thirty-four patients received rituximab for WAIHA in seven centres in the Republic of Ireland. The overall response rate was 70Á6% (24/34) with 26Á5% (9/34) achieving a complete response (CR). The time to response was 1 month post-initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 16 publications
0
33
0
2
Order By: Relevance
“…35,38 In a recent multicenter retrospective study, the time to response was one month post-initiation of rituximab in 87.5% and three months in 12.5% of patients. 39 It is worth remembering that rituximab re-treatment may be effective 35,39,40 and some patients responded to re-treatment more than once. 34,35 Rituximab has also been found to be effective in Evans syndrome with a reported overall response of 83% (66% complete).…”
mentioning
confidence: 99%
“…35,38 In a recent multicenter retrospective study, the time to response was one month post-initiation of rituximab in 87.5% and three months in 12.5% of patients. 39 It is worth remembering that rituximab re-treatment may be effective 35,39,40 and some patients responded to re-treatment more than once. 34,35 Rituximab has also been found to be effective in Evans syndrome with a reported overall response of 83% (66% complete).…”
mentioning
confidence: 99%
“…Another study by Bussone, et al, demonstrated a 93% of overall initial response to rituximab therapy with standard doses [44]. Relapse is unavoidable during follow up periods but retreatment with rituximab is effective in these patients [44,45]. Since patients may benefit from second course of rituximab, intermittent or a maintenance therapy should be considered.…”
Section: Rituximabmentioning
confidence: 99%
“…2,23,[25][26][27] In 4 studies, responses in wAIHA and cold agglutinin disease (CAD) were compared and were found superior in wAIHA in 3 studies, 2,23,25 whereas no difference in response rate was observed in the study of Peñalver et al In the GIMEMA study, this difference was noted in patients given low-dose rituximab, whereas no significant difference in response rate was found after treatment with a conventional dose of rituximab. 2 In addition, in the same study, an increased response rate was associated with young age and with a shorter interval between treatment and diagnosis only in patients given low-dose rituximab.…”
Section: How Does Rituximab Work?mentioning
confidence: 99%
“…Recent studies with longer follow-up show that responses up to 3 years are sustained in a proportion of patients (up to 30%). 26,43 Whether some patients can be considered cured after rituximab administration is not clear, given the lack of long-term follow-up in most published series. Maintenance therapy with rituximab aiming to prolong duration of response has not been investigated in this setting.…”
Section: Optimal Dose Of Rituximab and Duration Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation